(untitled) - Lawrence S Ritter (Reading, Massachusetts, 1996)
The book is divided into six main parts. Part One briefly introduces the role of money, markets, and institutions within the framework of the overall economy. Part Two launches an intensive of financial instruments and markets. Part Three discusses financial institutions. Part Four sets the stage for the unique analysis of financial system architecture. Part Five and Six deal with the art of central banking and monetary theory
Keywords: banks and banking,finance,money